Bladder cancer‐associated transcript 2 contributes to nephroblastoma progression. (11th January 2022) - Zhu, Jie; Zhu, Zhenwei; Cai, Peng; Gu, Zhicheng; Wang, Jian
Abstract: Background: Nephroblastoma is a common pediatric kidney tumor. Existing evidence has indicated that long non‐coding RNAs (lncRNAs) may be associated with tumorigenesis such as nephroblastoma. However, the contribution of lncRNA bladder cancer‐associated transcript 2 (BLACAT2) to tumorigenesis and the postoperative nephroblastoma prognosis remains unknown. Methods: In total, 50 pairs of patient nephroblastoma and corresponding adjacent non‐tumorous tissues were analyzed for BLACAT2 expression. The underlying roles of BLACAT2 in nephroblastoma cells were also investigated. The BLACAT2 level was detected in four nephroblastoma cell lines and normal cell line NGC‐407 using a quantitative real‐time polymerase chain reaction. The potential influence of BLACAT2 on nephroblastoma cells was explored based on RNA interference technology in vitro and in vivo . Moreover, the microRNA targeted by BLACAT2 and its target gene were predicted and verified. Results: BLACAT2 silencing suppressed cell proliferation, colony formation and tumor growth in vivo and promoted cell apoptosis in vitro . Furthermore, BLACAT2 could directly bind to miR‐504‐3p, thereby decreasing miR‐504‐3p expression. In addition, the impact of miR‐504‐3p on proliferation, colony formation and nephroblastoma cell apoptosis was reversed by BLACAT2. Wnt11 was identified as a target of miR‐504‐3p. Conclusions: The present study revealed that a novel BLACAT2/miR‐504‐3p/Wnt11 axis is associated with nephroblastoma, where BLACAT2 is able to sponge miR‐504‐3p to down‐regulate Wnt11. Abstract : Wnt11 deletion inhibited cell proliferation and colony formation and induced cell apoptosis in nephroblastoma cells.